Current Trend of MOFs Incorporated Membranes for Advanced Wastewater Treatment - Utomo, Dani Puji; Kusworo, Tutuk Djoko; Kumoro, Andri Cahyo; Budiyono, Budiyono; Kurniawan, Tonni Agustiono (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Membrane technology has gained attention in wastewater treatment due to its great potential for producing high-grade water products for reuse. The membrane also effectively removes persistent pollutants in water effluent. However, their application is constrained by low productivity due to fouling formation. Incorporating functionalized nanoparticles into polymeric membranes has attracted much attention due to the improved membrane performance and additional features. Metal-organic frameworks (MOFs) incorporated into polymeric membranes have been widely applied in reverse osmosis (RO), forward osmosis (FO), nanofiltration (NF), and microfiltration (MF) for water and wastewater treatment. This short review presented recent findings, fabrication methods, and a systematic understanding of transport mechanisms under various operating conditions. This study also focused on several important parameters, such as improving physicochemical properties, membrane features, and performance enhancement in wastewater treatment. The reported studies show that MOFs incorporated membranes have reached >95% organic pollutants and 100% suspended solids. The membrane durability was also enhanced up to 140%, and the flux recovery can be maintained at 98% after several cycles. Even some MOFs, such as ZIF-8 and UiO-66, exhibited excellent performance in harsh conditions (pH < 4). The prospects and challenges of MOFs-incorporated membranes in industrial applications were also provided in this study.